Causal Relationship between Money, Price and Income in Asian Countries (1964-2011) - Gyanwaly, Ram Prasad (Economic Journal of Nepal, 2012)
Monetary and fiscal policies are used for macroeconomic stabilization and to achieve low level of inflation and high level of economic growth. To execute these policies direction of causality between money, price, and income should be known. It is in this connection that this study examined the direction of causality between money, price and income in Asian countries namely- Nepal, India, Sri Lanka, Myanmar and Korea using the annual time series data of the period 1964-2011. Bivariate Granger causality test was performed for both non-cointegrated and cointegrated variables using conventional Granger F test and ECM models respectively. Causal nexus between these variables, in some extent, differed from one structure of economy to another but in all countries money was causing price and income. Feedback effects were coming either from price or income or the both. Thus, this study reaches to the conclusion that money supply is an endogenous variable in all the countries, though the extent of endogeneity in term of price and income variables slightly differs from one to another. Thus conventional concept of purely exogenous money supply is invalid. Money causes the both price and income and is receiving the feedback effects either from price or income or the both. The Economic Journal of Nepal, Vol. 35, No. 1, January-March 2012 (Issue N0. 137)